Identifying reactive organo-selenium precursors in the synthesis of CdSe nanoplatelets - Riedinger, Andreas; Mule, Aniket S.; Knüsel, Philippe N.; Ott, Florian D.; Rossinelli, Aurelio A.; Norris, David J. (Chemical communications (Cambridge, England), 2018)
In the synthesis of CdSe nanoplatelets, the selenium-to-selenide reduction pathway is unknown. We study solvent-free growth of CdSe nanoplatelets and identify bis(acyl) selenides as key reactive intermediates. Based on our findings, we prepare a series of bis(acyl) selenides that provide useful precursors with tailored reactivity for liquid-phase syntheses of nanoplatelets.